2009
DOI: 10.1111/j.1749-6632.2009.04874.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the NF‐κB Complex in the Inflammatory Exudates Characterizing the Idiopathic Inflammatory Myopathies

Abstract: The transcription factor nuclear factor-kappaB (NF-kappaB) is a ubiquitously expressed protein family that is considered crucial in autoimmunity. We describe NF-kappaB p50 and p65, and the inhibitor I-kappaB alpha in the inflammatory exudates characteristic for the different idiopathic inflammatory myopathies (IIM), that is, endomysial CD8(+) cytotoxic T cells invading non-necrotic fibers in polymyositis (PM) and sporadic inclusion body myositis (sIBM), and the perimysial/perivascular CD20(+) B cells and CD4(+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Similar prevalence of CD4+ and CD8+ T cells were observed (Fig. 8 and not shown), reminiscent of recent reports in sIBM (Creus et al, 2009; Pandya et al, 2010). Centralized nuclei in both severely affected (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar prevalence of CD4+ and CD8+ T cells were observed (Fig. 8 and not shown), reminiscent of recent reports in sIBM (Creus et al, 2009; Pandya et al, 2010). Centralized nuclei in both severely affected (Fig.…”
Section: Resultssupporting
confidence: 90%
“…There is no agreement however, as to their relative contributions to the initiation and progression of disease (Greenberg, 2009). The in-flammatory component consists of scattered infiltrates of cytotoxic CD8+ (and CD4+) T lymphocytes and macrophages (Creus et al, 2009; Dimitri et al, 2006; Pandya et al, 2010), invasion of MHC-1 bearing myofibers and overexpression of pro-inflammatory chemokines and cytokines (Confalonieri et al, 2000; Raju et al, 2003; Tews and Goebel, 1996). These immune characteristics are shared with polymyositis (PM).…”
Section: Discussionmentioning
confidence: 99%
“…In human IIM, NF-κB activation has been demonstrated by western blot analysis and electrophoretic mobility shift assays on muscle biopsies in patients with PM and DM [38]. Furthermore, NF-κB p50 and p65 is found in CD4 + T cells in muscle biopsies from both PM and IBM [5]. In human IBM and a myositis mouse model, overexpression of MHC Class I on muscle fibres results in activation of NF-κB and an endoplasmic reticulum stress response [4, 39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is thought to induce protein loss via oxidative activation of the myogenic transcription factor nuclear factor-kappa B (NF-κB). Furthermore, NF-κB p50 and p65 have been described within the inflammatory exudates of different IIM subtypes [5]. Several genes have been identified that share homology with the NF-κB family of proteins, including NFKB1 , NFKB1A , NFKB1B , NFKB1E , IKBL (NFKBIL1) , REL , RELB and BCL3 .…”
Section: Introductionmentioning
confidence: 99%
“…The p50 and p65 NF-kB subunits have been described in inflammatory exudates of polymyositis and IBM [7]. A candidate gene study [8] tested for genetic associations between eight genes of the NF-kB family of proteins and IIMs.…”
Section: Nf-kb Gene Polymorphisms Are Not Independent Risk Factors Fomentioning
confidence: 99%